« À la recherche des Macédoniens » : le regard des cartes, 1840-1918 - Joëlle Dalègre (Cahiers Balkaniques, 2011)
The expression ’Balkan peninsula’ was first employed in 1808 by August Zeune. In 1821 another German, d’Oetzel, drew the first map of the European populations. The maps continued multiplying until 1920. Little by little the techniques as well as the knowledge of the various regions and populations became more precise. The maps became a propaganda tool, in as much as they attributed—depending on the cartographer—Macedonian territory to the Greeks, the Serbs or, most often, the Bulgarians. In 1906, the Serb Cvijic, the first, situated on a map, the “macédoslaves”. This communication outlines the principal stages of this cartographic evolution, which eventually situated the “Macedonians” in none other than… Macedonia.